Using alendronic acid coupled fluorescently labelled SM liposomes as a vehicle for bone targeting - Medina, Oula Penate; Medina, Tuula Penate; Humbert, Jana; Qi, Bao; Baum, Wolfgang; Will, Olga; Damm, Timo; Glueer, Claus (Current Pharmaceutical Design, 2020)
Background: We recently developed a liposomal nanoparticle system that can be used for drug delivery and simultaneously be monitored by optical or photoacoustic imaging devices. Here we tested the efficacy of alendronate as a homing molecule in SM-liposomes for bone targeting. Methods: Alendronate was immobilized covalently on the liposomal surface and the fluorescent dye indocyanine green was used as a payload in the liposomes. The indocyanine green delivery was analyzed by 3D optical tomography, optical fluorescence scanner, photoacoustic imaging, and by ex-vivo biodistribution studies. Results: The results show that the alendronate, coupled to the liposomal surface, increases sphingomyelin containing liposome targeting up to several-folds. Conclusion: The alendronate targeted liposomes open possibilities for an application in active bone targeting.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Alendronic acid; ICG; Liposomes; Multimodal imaging; Sphingomyelin